(De)Colonized Science: Hopes, Complexities, Tensions, and Frustrations in Seeking to Indigenize Undergraduate Science Education - Kahpeaysewat, Nikita; Lemieux, Collette; Hill, Joshua (Imagining SoTL)

(untitled) (Mount Royal University Library in partnership with University of Alberta Library, 2023)
This article is an exploration of our efforts to develop an Indigenous Science Course at Mount Royal University (MRU) located in Mohkinstsis within the Ancestral Lands of the Blackfoot Confederacy the Territory of the Treaty 7 signatories Kainai, Piikani, Siksika, Tsuut’ina, Bearspaw, Chiniki, and Wesley Nations and the Metis Nation Region III. The authors are an Indigenous environmental scientist and recent MRU graduate (Nikita), a settler assistant professor (Collette), and an Indigenous assistant professor (Joshua). We engage here as an enactment of research as ceremony (Wilson, 2008). We draw on Metissage storywork to spark meaning making of our experiences in seeking to contribute to the Indigenization of our University (Archibald, 2008). We believe that the stories we share have the potential to open up interpretive possibilities for those interested in Scholarship of Teaching and Learning as Reconciliation (Hill, 2022) and decolonization and Indigenization of post secondary education more broadly (Battiste, 2013). Through storytelling we endeavor to push for change in sharing the hopes, complexities, tensions, and frustrations we encountered.